What clinical features precede the onset of bipolar disorder?. (March 2015) - Perich, Tania; Lau, Phoebe; Hadzi-Pavlovic, Dusan; Roberts, Gloria; Frankland, Andrew; Wright, Adam; Green, Melissa; Breakspear, Michael; Corry, Justine; Radlinska, Basia; McCormack, Clare; Joslyn, Cassandra; et al.
Abstract: Despite a growing number of reports, there is still limited knowledge of the clinical features that precede the onset of bipolar disorder (BD). To explore this, we investigated baseline data from a prospectively evaluated longitudinal cohort of subjects aged 12–30 years to compare: first, lifetime rates of clinical features between a) subjects at increased genetic risk for developing BD ('AR'), b) participants from families without mental illness ('controls'), and c) those with established BD; and, second, prior clinical features that predict the later onset of affective disorders in these same three groups. This is the first study to report such comparisons between these three groups (though certainly not the first to compare AR and control samples). 118 AR participants with a parent or sibling with BD (including 102 with a BD parent), 110 controls, and 44 BD subjects were assessed using semi-structured interviews. AR subjects had significantly increased lifetime risks for depressive, anxiety and behavioural disorders compared to controls. Unlike prior reports, preceding anxiety and behavioural disorders were not found to increase risk for later onset of affective disorders in the AR sample, perhaps due to limited sample size. However, preceding behavioural disorders did predict later onset of affective disorders in the BD sample. The findings that i) AR subjects had higher rates of depressive, anxiety and behavioural disorders compared to controls, and ii) prior behavioural disorders increased the risk to later development of affective disorders in the BD group, suggest the possibility of therapeutic targeting for these disorders in those at high genetic risk for BD. Highlights: Those at high genetic risk for bipolar disorder had significantly increased lifetime risks for depressive, anxiety and behavioural disorders. Preceding anxiety and behavioural disorders were not found to increase risk for later onset of affective disorders in the at-risk sample. Preceding behavioural disorders did predict later onset of affective disorders in the bipolar disorder sample. There is a possibility of therapeutic targeting for depressive, anxiety and behavioural disorders in those at high genetic risk.